Qadliyyah Al-Hudud fi Al-Hayah Al-Usriyyah: Tahlil Tafsir Jami' Li Ahkam al-Quran Li al-Imam al-Qurthubi (قضية الحدود في الحياة الأسرية: تحليل تفسير جامع لأحكام القرآن للإمام القرطبي) - Rifaannudin, Mahmud; Badrun, Muhammad; Arlisah, Arlisah; Rochmad, Rochmad (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
Purposestudy aims to explore the concept of hudud and its relationship with family treatment according to Imam Al-Qurtubi.MethodThis research employs a library research method, using documentation as a data collection technique. To analyze hudud, this study utilizes a thematic approach. This study is relevant and closely related to the interpretation of the Qur’an as it is capable of establishing sharī‘ah at any time and place, setting legal rulings that align with contemporary challenges and the diversity faced today. Results/findingsAllah mentions the word hudūd in the Qur’an to refer to family boundaries, such as marital relations (ar-rafats), zihar, divorce, and inheritance distribution. These hudud are divided into two categories prescriptive hudud and prohibitive hudud. ConclusionThe conclusion of the research on hudud remain applicable in the modern era as divine legislation that ensures justice and social balance. From an Islamic feminist perspective, hudud does not constitute discrimination against women but rather guarantees their rights and protection. Therefore, instead of rejecting them, hudud should be understood and implemented in ways that align with contemporary developments while maintaining principles of justice and equality, fostering a cohesive society that respects women's rights.